Regional differences in density-dependent mortality and reproduction in Finnish reindeer - Kojola, Ilpo; Helle, Timo (Rangifer, 1993)
Reindeer in the southern and central regions of reindeer husbandry in Finland feed on arboreal lichens or are given supplementary rations from midwinter whereas in the northern region reindeer use snow-covered forage throughout winter. Rates of mortality and reproduction were examined using data from population crashes of semi-domesticated reindeer that occurred in Northern Finland during 1960-1987. The mortality and reproductive rate were density-dependent in the southern region and the mortality was density-dependent in the central region. The density-dependence was most probably due to food competition in forest cutting areas where reindeer gather to feed on arboreal lichens from felled trees. In the northern region mortality was not density-dependent indicating that where reindeer feed on over-utilized winter range the effects of increased feeding competition are masked by very large changes in the availability of forage.